Quality Assurance in Higher Education as a Political Process - Skolnik, Michael L. (My University, 2009)
Is quality assurance in higher education a technical process or a political process? Michael Skolnik suggests three reasons why quality assurance should, in many cases, be viewed as a largely political process: 1) The considerable differences of opinion among different stakeholders about the definition of quality 2) The likelihood that quality assurance serves as a vehicle for the pressures toward conformity within academe 3) The tendency to exclude some stakeholders, particularly faculty, from a significant role in the design and implementation of quality assurance processes Skolnik concludes that it would be better to accept Louise Morley's claim that quality assurance is "a socially constructed domain of power" and design assessment processes in a way that fits their political nature. He further suggests that employing a responsive model of evaluation could make quality assurance more effective. The responsive model evaluation is a collaborative process that starts with the claims, concerns, and issues put forth by all stakeholders.
Keywords: Accountability, Autonomy, and Politics; Leadership and Governance